Rosie the riveter : women working on the home front in World War II - Colman, Penny (New York : Crown Publishers, 1995)
Describes how working conditions changed during World War II, when women held many different jobs.
ONE War! "How are things going to change?" -- TWO Home front "the exit of life-as-usual -- THREE Extraordinary opportunities for women "Rosie the Riveter" -- FOUR Getting ready for war "the great arsenal for democracy" -- FIVE The First six months "Job, jobs, jobs" -- SIX The War years wear on "I'll do anything for my country" -- SEVEN The Final war years "It's a man's and woman's world" -- EIGHT Pioneers in the American workplace I had a chance to prove that I could do something" -- NINE Peace "the men had been promised their jobs when they came back." -- Select list of women's wartime jobs -- Facts & figures about women war workers -- Chronology.
Includes bibliographical references (p. [110]-113) 0and index.
Keywords: Women -- Employment -- United States -- History -- 20th century -- Juvenile literature; World War, 1939-1945 -- Women -- United States -- Juvenile literature